1990
DOI: 10.1093/carcin/11.5.835
|View full text |Cite
|
Sign up to set email alerts
|

Liver hyperplasia is not necessarily associated with increased expression of c-fos and c-myc mRNA

Abstract: Experiments were designed to investigate the expression of three cell-cycle-dependent proto-oncogenes in response to two different types of proliferative stimuli: compensatory cell proliferation after partial hepatectomy (PH) or CCl4 and liver hyperplasia induced by the mitogens ethylene dibromide (EDB) and cyproterone acetate (CPA). Steady-state levels of messenger RNAs for c-fos and c-myc were found to be elevated after PH or CCl4 with a maximum increase between 0.5 and 2 h for c-fos and at 2-3 h for c-myc a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
13
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 0 publications
6
13
0
Order By: Relevance
“…The results clearly show that no increase in steady state levels of c-fos occurs following treatment with both mitogens ( Figure 1A and B). This ®nding is in agreement with our previous results indicating that c-fos is not required for rat liver cell proliferation induced by cyproterone acetate and nafenopin (Coni et al, 1990). Following these studies, additional evidence has been accumulated indicating that increased c-fos expression is not necessary for hepatocyte proliferation induced by six dierent mitogens (Coni et al, 1993;Goldsworthy et al, 1994;Ohmura et al, 1996a).…”
Section: Histologysupporting
confidence: 91%
See 3 more Smart Citations
“…The results clearly show that no increase in steady state levels of c-fos occurs following treatment with both mitogens ( Figure 1A and B). This ®nding is in agreement with our previous results indicating that c-fos is not required for rat liver cell proliferation induced by cyproterone acetate and nafenopin (Coni et al, 1990). Following these studies, additional evidence has been accumulated indicating that increased c-fos expression is not necessary for hepatocyte proliferation induced by six dierent mitogens (Coni et al, 1993;Goldsworthy et al, 1994;Ohmura et al, 1996a).…”
Section: Histologysupporting
confidence: 91%
“…In particular, it has been previously shown that direct hyperplasia induced by primary mitogens may be induced in the complete or partial absence of modi®cations in the expression of immediate early genes such as c-fos, c-jun and LRF-1 (Coni et al, 1990(Coni et al, , 1993Ohmura et al, 1996a). Therefore, we have determined the pattern of modi®cations of these genes during direct hyperplasia induced in mouse liver by two distinct mitogens, TCPOBOP and EDB.…”
Section: Histologymentioning
confidence: 98%
See 2 more Smart Citations
“…DNA polymerase B seems to be one of the most important enzymes involved in the repair of damaged DNA because of its preference for short gaps formed during excision repair [2]. Recent studies show a different distribution of DNA polymerase B activity, as well as of the levels of its mRNA, in tissues of mouse [3] and rat 141.…”
Section: Introductionmentioning
confidence: 99%